Reformasi Hukum Pidana Islam Kontemporer (Studi atas Pemikiran Abdullah Ahmed an-Naim) (Jurnal Hukum Islam, 2019)
The application of Islamic criminal law (fiqh jinayah) into the nation-state system of government demonstrates the vision that some Muslims have been fighting for. This manifestation is frequently indicated by the implementation of hudud matters, including the punishment of cutting off hands, stoning, beating, and qisas (capital punishment), to illustrate how “Islamic” a ruling regime is. The present study seeks two research questions, namely: (1) why is the Islamic criminal law being stagnant? (2) How is An-Naim’s thought in reforming Islamic criminal law? Grounded in qualitative library research, this study employed a philosophical approach. Descriptive-analytical and interpretive methods were used to analyze the obtained data. The findings expose that the reality of the application of sharia law by the state, according to an- Naim, as occurred in Sudan during the era of President Numeiri, was more political in nature. In order to lead to applicable and contemporary Islamic criminal law, an-Naim offers that the applied law must be in accordance with constitutional and international standards concerning two considerations, namely: the principle of legality without any discrimination and the issue of punishment and treatment of prisoners.